Implementation of Sustainable Transportation at Mahidol University, Salaya Campus, Thailand - Charmondusit, Kitikorn; Wattanawinitchai, Waratip; Mahisavariya, Banchong (Journal of Sustainability Perspectives, 2022)
Mahidol University is one of the leading sustainable universities in Thailand, which recognizes the importance of combining actions to achieve the 17 Sustainable Development Goals of the United Nations (17 Sustainable Development Goals: 17 SDGs) and the concept of Sufficiency Economy Philosophy. The eco-university and sustainability policy was launched and implemented in 2021 in order to reach the 17 SDGs. Transportation is one of the important issues of campus development. In order to reduce the greenhouse gas emission from private fossil based fuel transportation, the public transportation both inside and outside the campus area is provided including electric tram, shuttle bus and public bicycle. An Electric cart with solar energy was initiated and used on campus. Walking and cycling as primary means for commuting on campus have been promoted by reduction of vehicle traffic. Cycling lanes are improved and bicycle racks are provided around the campus. Around more than 10,000 bicycles including more than 500 public bicycles were used on campus. The parking areas were constructed and adjusted into green open spaces. Many outdoor spaces are created to support various kinds of activities and gatherings enhancing liveliness and variety to campus lifeKeyword: Mahidol University, Mobility, Transportation, Green area, Sustainability campus